Bio-ethanol steam reforming on Ni based catalyst. Kinetic study - Llera, I. (2012)
In this work a kinetic study of steam reforming of ethanol using a nickel based catalyst in the temperature range 873?923 K was performed. Conversion monotonically increases with space time and temperature. At 923 K we obtained more than 5 mol of hydrogen per mole of ethanol. This hydrogen yield is high compared to values reported in the literature. CO yield increases with the space time and temperature while CO2 yield has a maximum at 923 K, which coincides with the space time at which the system reaches complete conversion. At larger residence time CO2 yield decreases. CH4 yield is very low for all conditions studied but a maximum can also be seen with space time. Both CO2 and CH4 are intermediate products, while CO is a final product. The effect of adding H2 to the feed was studied. Analyzing the kinetic results we propose a model involving the following reactions: (E1) CH3CH2OH = CO + CH4 + H2 (E1) CH3CH2OH + H2O = CO2 + CH4 + 2H2 (R1) CH4 + 2H2O=2CO2 + 4H2 (R2) CO2 + H2 = 2CO + H2O The first two involving ethanol are irreversible while the latter two are reversible. The surface reactions are the rate determining steps. Kinetic parameters were estimated using commercial software.